Clinical and Radiological Follow-up of Subjects with Chronic Asymptomatic Pancreatic Hyperenzymemia - Granato, Anna; Amodio, Antonio; De Pretis, Nicolò; De Marchi, Giuilia; Tumelero, Tiziana; Goni, Elisabetta; Gabbrielli, Armando; Vantini, Italo; Benini, Luigi; Frulloni, Luca (JOP. Journal of the Pancreas, 2013)
Context Chronic asymptomatic pancreatic hyperenzymemia (CAPH) has been described since 1996 as a benign disease. Pathological findings at magnetic resonance cholangiopancreatography (MRCP) with secretin stimulation (s-MRCP) have been found in 50% of CAPH subjects, but in 30% their clinical meaning remains undefined. Objective To investigate subjects with CAPH during the follow-up to assess the clinical and radiological outcome. Methods From January 2012 to March 2013, a cohort of 160 subjects previously studied for CAPH were re-evaluate with s-MRCP and biochemical tests. Results Clinical data relative to 108 subjects were collected, whereas 68 (47 males, 21 females; mean age: 49.8 ± 12.2 years) underwent s-MRCP. Clinically, acute pancreatitis was observed in one subject out of 108 (0.9%) after 5 years from the first detection of hyperenzymemia. Among the 68 subjects who underwent s-MRCP, 23 (33.8%) had previous s-RMCP normal and 45 (66.2%) pathological. No radiological alterations in 23 subjects with normal s-MRCP at first evaluation were observed at follow-up, whereas unchanged s-MRCP was documented in 41 out of 45 (91.1%) subjects with pathological s-MRCP at first evaluation after mean follow-up of 3±2 years. One out of 11 subject with IPMN had progression of the size of the cyst, 1 out of 11 with suspected sphincter of Oddi dysfunction showed an increase of Wirsung duct diameter, while a worsening of ductal morphology was observed in 2 out of 20 subjects with suspected chronic pancreatitis. Conclusion CAPH subjects remain asymptomatic during the follow-up. Subjects with previous normal MRCP-s did not show pathological findings at follow-up whereas only a small percentage of those with previous suspected sphincter of Oddi dysfunction or chronic pancreatitis, showed a progression at imaging in a short term follow-up.